Infecciones vaginales en pacientes de 20 a 40 años de edad, en el hospital del día Instituto Ecuatoriano de Seguridad Social (IESS) de Zamora durante el periodo 2014 - Villagómez Lojano, Somayra Beatriz (2015)
It is a descriptive study, field and of traverse carried out in the Hospital Of the Day Ecuadorian Institute of Social security (IESS) of Zamora of Zamora's parish, canton Zamora, County Of Zamora Chinchipe, was interviewed 120 women that are assisted in the gynecology area, during the period January - I Wither of the 2014, with the purpose of identifying the vaginal infections in users from 20 to 40 years of age. Most of the studied feminine population, they are young women of among 26 to 31 years with 66 women that it corresponds to 55%, 85% you autoidentificaron like you crossbreed, 37,50% has the level of escolaridadpreuniversitaria, 59.17% is public servants. It was investigated on the level of knowledge it has more than enough vaginal infections: of which 95% knows on the topic. The interviewed women presented sintomatología manifested by itch in 52.50%. 61.22% has been assisted previously by vaginal infections that were detected by means of laboratory exams, receiving the corresponding treatment, of the interviewed women 60.83% knows the reasons and factors that predispose to acquire vaginal infections. You concludes that the causal agent of the vaginal infections with 37.50% was the gardnerella, 31.67 candid% and the 30.83 tricomona. A training plan was developed to improve the knowledge of the women, and the application of preventive measures and opportune treatment of the vaginal infections